Leading through language : choosing words that influence and inspire / Bart Egnal. - Egnal, Bart,
"Become a more effective leader--cut the jargon and say what you mean Leveraging. Strategizing. Opening the kimono. Unlocking human capital. Trying to nail that BHAG. All on a go forward basis. These are only a few examples of the jargon-ridden language that is too often the mainstay of business communication. Jargon frustrates, confuses, and generally alienates listeners. Yet it's also everywhere, and using it can often seem like a mandatory requirement for anyone who wants to establish credibility in a professional workplace. To be an effective leader, you must be brave enough to be the first to drop jargon in favor of simple, coherent language. This can be difficult if you've spent years immersed in business culture, but Leading Through Language will show just how much you've come to rely on jargon, why it's holding you back, and how to trim it away to more effectively convey information and ideas. Understand why jargon is reviled, yet ubiquitous Learn why "business speak" gets in the way of business Discover what kind of language influences and inspires others Convey ideas with clarity, energy, and conviction Approach all communication as an act of leadership Communication often falls by the wayside in favor of more measurable data-backed performance metrics; but good communication has the power to improve metrics in every area of an organization. Leading Through Language is the business world's much-needed guide to true leadership communication, showing you how to eliminate idle talk and master compelling communication"-- "Language in the business world is getting in the way of effective leadership. This book examines why language in the workplace is dull, confusing, or simply ineffective. It also considers why these failings undermine those who wish to demonstrate leadership when they speak. The solution is to use the language of leadership, a language that clearly and powerfully brings your ideas to life for your audience. This book teaches how to use words that engage and inspire everyone you speak with or write to. It will explain how to approach all communication as an act of leadership and then to use language that can convey ideas with energy, clarity, and conviction"--